Ocular Anomalies in a Neonate: A Case Report on Right Eye Anophthalmos and Left Eye Microphthalmos - Vignesh, Venugopal; Aswin, John; Abinish, Dyneese Geetha; Lokeshvaran, Deivendran; Kalaivani, Sivakumar (Indian Journal of Pharmacy Practice)
Anophthalmia is characterised by the complete absence of optic structures, while microphthalmia involves underdeveloped eye structures, often accompanied by other defects such as congenital cataracts and coloboma. Both conditions can be unilateral or bilateral and are linked to genetic mutations. Epidemiological studies show a prevalence of 3.0 per 10,000 live births for these anomalies, with maternal factors like advanced age and diabetes being significant risk factors. This case presents a female neonate, born via emergency caesarean section, presented with right eye anophthalmos and left eye microphthalmos. The mother had right eye incomplete cryptophthalmos and left eye microphthalmos, with no family history of congenital disorders or consanguinity. Examination revealed the infant weighed 2.5 kg and had normal neonatal reflexes with normal neurological function. No other external anomalies were found. The left eye was small and malformed with short eyelids, while the right eye orbit was absent. The ophthalmologist confirmed the diagnosis and tobramycin eye ointment was prescribed to prevent bacterial infections. The infant was discharged after receiving thorough parental counselling on the condition's nature, prognosis, potential interventions and the importance of regular follow-ups. In conclusion, this case illustrates the complexity of anophthalmia and microphthalmia, underscoring the need for thorough postnatal examinations and genetic counselling. Accurate diagnosis and personalised management rely on understanding the genetic basis of these conditions. Future research should focus on clarifying genetic pathways to enhance diagnostic and therapeutic approaches.
Keywords: Anophthalmos; Microphthalmos; Coloboma; Congenital Abnormalities; Case report